Visualisasi Video Pembelajaran dalam Melatih Kemampuan Mencuci Tangan bagi Anak Tunagrahita Kategori Sedang di SLB Negeri 2 Padang - Dari, Wildan; Irdamurni, Irdamurni (Indonesian Journal of Islamic Early Childhood Education, 2019)
This research is motivated by a problem found in class VII SLB Negeri 2 Padang in moderate retardation students in January 2019. Researchers found a student who could not wash their hands properly. This study aims to determine whether the training method using effective learning videos to improve the ability to wash hands. This study uses a class action research method consisting of two cycles, each cycle consisting of planning, action, observation and reflection. The results of the study in the initial conditions were 12.90%. After the first cycle, the results of the first meeting (22.58%), the second meeting (32.25%), the third meeting (38.70%) and the fourth meeting (48.38). The results of the second cycle of the first meeting (58.06%), the second meeting (67.74%), the third meeting (74.19%) and the fourth meeting (77.41%). These results indicate that the training method using video learning can improve the ability to wash hands for mentally retarded students in the moderate category. From these results it can be seen that the training method with learning videos can improve the ability to wash hands.